Aktivitas Antioksidan Kombinasi Ekstrak Etanol 96 % Kulit Buah Markisa Ungu dan Kuning secara In-Vitro - Fitria, Laila; Ngibad, Khoirul (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2022)
This study aimed to find the best combination of 96% ethanol extract from purple passion fruit (Passiflora edulis f. edulis Sims) peel and yellow passion fruit (Passiflora edulis Sims f. flavicarpa Deg) peel as in vitro antioxidants using the DPPH method. The 96% ethanol extract of purple and yellow passion fruit peel was obtained by the maceration method using 96% ethanol solvent. The combination treatment of purple and yellow passion fruit peel extracts was made with three comparisons of namely 1:1, 2:1, and 1:2, respectively. In vitro, antioxidant activity was assayed using the DPPH method to obtain the IC50 value. The results showed that the best combination of extracts as in vitro antioxidants was the combination of 96% ethanol extract from purple and yellow passion fruit peel with ratio (1:1) of 12.45 mg/L followed by the combination of extracts 1:2 (51.31 mg/L) and 2:1 (66.23 mg/L). In conclusion, the results suggest that the extracts combination of purple and yellow passion fruit peel with a ratio (1:1) can increase in vitro antioxidant activity.